Laboratory Standard Operating Procedures (SOP) for the evaluation of rice grain appearance - Loaiza De La Pava, Johana Katerine; Giraldo Ossa, Erika Fernanda; Mona Cortes, Andrea Fernanda; Graterol Matute, Eduardo Jose (2025)
This standard operating procedure (SOP) outlines the evaluation of grain appearance in rice germplasm, with a focus on quantifying white core, measuring grain length and width, and calculating the length-to-width ratio.